2001
DOI: 10.1016/s0006-3495(01)76084-5
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic Electron Transfer Controlled by Protein Relaxation: Analysis by Langevin Stochastic Approach

Abstract: Relaxation processes in proteins range in time from picoseconds to seconds. Correspondingly, biological electron transfer (ET) could be controlled by slow protein relaxation. We used the Langevin stochastic approach to describe this type of ET dynamics. Two different types of kinetic behavior were revealed, namely: oscillating ET (that could occur at picoseconds) and monotonically relaxing ET. On a longer time scale, the ET dynamics can include two different kinetic components. The faster one reflects the init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 110 publications
(165 reference statements)
0
73
0
Order By: Relevance
“…The classical stochastic Langevin equation together with Marcus theory and the approach of two vibrational modes was used to calculate the rate of primary electron transfer, controlled by protein relaxation (Cherepanov et al 2001). A lot of experimental and theoretical studies have clearly shown that, in real RCs, many vibrational modes contribute to primary events, and that these events occur on a timescale comparable with the characteristic time of vibrational thermalization (for related reviews see Shuvalov 2000;Yakovlev 2013;Parson and Warshel 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The classical stochastic Langevin equation together with Marcus theory and the approach of two vibrational modes was used to calculate the rate of primary electron transfer, controlled by protein relaxation (Cherepanov et al 2001). A lot of experimental and theoretical studies have clearly shown that, in real RCs, many vibrational modes contribute to primary events, and that these events occur on a timescale comparable with the characteristic time of vibrational thermalization (for related reviews see Shuvalov 2000;Yakovlev 2013;Parson and Warshel 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical elucidations of the oscillatory behavior have been also worked [23,[28][29][30]. These theories in the CT complexes may relate to BJ theory in ET, but not to M theory and KM theory.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, it has been proposed that the gating event is a transition of the ubiquinone between its 'inactive' distal and 'active' proximal positions [6]. Based on the similarities between the above described fast and slow components of ET and PT respectively, we have speculated that the ET reaction is controlled not by one, but by two relaxation/gating modes [8]. In those RCs, where Q B was initially in the proximal position, the electron spillover from Q A ᭹− to Q B could be driven by proton redistribution that selectively stabilized the Q B ᭹− state (τ ∼ 100 µs and E a ∼ 10-20 kJ/mol).…”
Section: Tentative Gating Mechanismsmentioning
confidence: 99%
“…In those RCs, where Q B was initially in the proximal position, the electron spillover from Q A ᭹− to Q B could be driven by proton redistribution that selectively stabilized the Q B ᭹− state (τ ∼ 100 µs and E a ∼ 10-20 kJ/mol). If Q B was initially in the distal position, it had to be brought into the proximal position (τ ∼ 500 µs and E a ∼ 60 kJ/mol) before the ET and PT could take place [8]. In several recent papers, the role of Ser-L223 in the Q B ᭹− stabilization has been discussed [12,49,50].…”
Section: Tentative Gating Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation